EFFECTS OF A BOXING TRAINING PROGRAM ON THE CORPORAL COMPOSITION AND MUSCULAR ENDURANCE (Fiep Bulletin - online, 2012)
This study was conceived to evaluate the effects of a training boxing program in the corporal composition and muscular endurance in beginners. It was applied anthropometric and neuromuscular tests in twenty four persons, with age between 18 to 35 years old. The classes have had duration of 60 minutes for three times a week for three months. The results show a noticeable improvement at the corporal composition related to the fat mass, fat percentage, and body mass and also related to neuromuscular area, an improve at the resistance of arm flexion and series abdominal. The results show a noticeable improvement at the corporal composition related to the fat mass, fat percentage, and body mass and also related to neuromuscular area, an improvement of the endurance of the arm flexion and in the abdominal repetition series.
Keywords: Boxing; Corporal Composition; Muscular Endurance